2018
DOI: 10.3390/ijms19051334
|View full text |Cite
|
Sign up to set email alerts
|

ScFvs as Allosteric Inhibitors of VEGFR-2: Novel Tools to Harness VEGF Signaling

Abstract: Vascular Endothelial Growth Factor Receptor 2 (VEGFR-2) is the main mediator of angiogenic signaling in endothelial cells and a primary responder to VEGF. VEGF dependent VEGFR-2 activation regulates endothelial cell migration and proliferation, as well as vessel permeability. VEGF is presented as an antiparallel homodimer, and its binding to VEGFR-2 brings two receptors in close proximity. Downstream signaling is triggered by receptor dimerization, kinase activation, and receptor internalization. Our aim was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
(58 reference statements)
1
2
0
Order By: Relevance
“…An important feature of antibodies, affinity, represents the binding capacity between an antibody and its target antigen. The results of the sandwich ELISA demonstrated BsDb can bind to PD-1 and VEGF165 simultaneously, and the K aff values of binding reactions detected by indirect ELISA between the BsDb and VEGF165 and the BsDb and PD-1 were 124.78 nM and 25.07 nM, respectively, illustrating that the BsDb could bind strongly to VEGF165 and PD-1 simultaneously, which was favorably in agreement with other reported antibody fragments [ 35 ].…”
Section: Discussionsupporting
confidence: 86%
“…An important feature of antibodies, affinity, represents the binding capacity between an antibody and its target antigen. The results of the sandwich ELISA demonstrated BsDb can bind to PD-1 and VEGF165 simultaneously, and the K aff values of binding reactions detected by indirect ELISA between the BsDb and VEGF165 and the BsDb and PD-1 were 124.78 nM and 25.07 nM, respectively, illustrating that the BsDb could bind strongly to VEGF165 and PD-1 simultaneously, which was favorably in agreement with other reported antibody fragments [ 35 ].…”
Section: Discussionsupporting
confidence: 86%
“…The isolation of scFvs with apparent and predicted affinity in the subnanomolar range from a moderate diversity and synthetic phage scFv library (Tomlinson I, 3.8 × 10 8 ) in the current study is acceptable when compared with the affinity of anti-VEGFR-2 scFv candidates in the 137-6800 nM range, which were isolated from the highly diverse synthetic ETH-2 Gold library (3 × 10 9 antibody clones) through solid-phase biopanning. 36 In another study conducted by Böldicke et al, 37 an affinity of 3.8 nM was reported for one of the anti-VEGFR-2 scFvs (A7), isolated from a mouse immune library (undergoing in vivo affinity maturation through somatic mutation) and using a solid-phase selection approach. Taken together, these results underscore the capacity of SPB used in this study for the isolation of scFv clones, possibly with high affinity binding in the nanomolar range.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous reports, we found that concentrations of VEGF were significantly lower in PDR patients pretreated with IVI. As VEGF inhibitors, anti-VEGF drugs prevent VEGF from binding to VEGF receptors such as vascular endothelial growth factor receptor-2 (VEGFR-2), thereby inhibiting endothelial cell proliferation and reducing vascular leakage, thus eliminating fragile neovascularization or inhibiting its formation [21][22] . A large number of studies have confirmed that preoperative IVI combined with PPV in the treatment of PDR can not only reduce intraoperative and postoperative complications, but also improve the visual prognosis of patients [11][12][13] .…”
Section: Discussionmentioning
confidence: 99%